Microstructure of cement paste incorporating high volume of low-grade metakaolin. (February 2020) - Zhao, Diandian; Khoshnazar, Rahil
Abstract: The influence of low-grade metakaolin (MK) on the mechanical and microstructural properties of cement paste was studied through compressive strength test and microstructural analyses, including thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and X-ray photoelectron spectroscopy (XPS). The results indicated that cement paste incorporating MK with around 40 wt.% kaolinite content in raw clays achieved comparable 28-day strength to that of the reference even at 40 wt.% replacement level. Microstructural studies showed a considerable amount of portlandite consumption after 3 d and a refinement of pore structure in backscattered micrographs. The Al/Ca ratio of calcium-aluminosilicate-hydrate (C-A-S-H) increased upon the increased replacement levels, while Ca/Si decreased due to the introduction of MK, but it did not further reduce with the increased MK content. The binding energy of Si 2p, Al 2p and Ca 2p spectra increased due to the incorporation of MK.